APAKAH STRUKTUR KEPEMILIKAN MEMPENGARUHI PENGHINDARAN PAJAK? BUKTI EMPIRIS DARI PASAR MODAL INDONESIA - Fauzan Fuadi; Riska Agi Sawirti; Fitria Fertha Agustina; Andi Mulyono; Ratih Tiyas Pratiwi (Faculty of Economics and Business, 2024)
Tax avoidance is an effort by company management to reduce tax payments. This study aims to examine the relationship between ownership structure and tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange. Furthermore, this research divides ownership structure into five variables, namely managerial ownership, institutional ownership, family ownership, government ownership, and foreign ownership. The study utilizes secondary data with a purposive sampling approach and selects a total of 300 firm-year observations. Regression analysis is employed to test the research hypotheses. The results of the study indicate that managerial, foreign, and family ownership structures have an impact on tax avoidance Keywords: Tax Avoidance, Ownership Structure, Family Ownership, Managerial Ownership, Foreign Ownership